Effective multisensory multimedia model for engaging literacy instruction in first grade - Kinney, Jeanne (My University, 2013)
This action research project was undertaken to determine if a multisensory, multimodal approach to comprehensive reading instruction would be effective, as well as engaging, for students in a coeducational, public, first grade classroom. The first phase involved classroom study incorporating multimodal approaches to guided reading groups and whole group instruction and the second phase measured engagement of iPad usage during multisensory word study instruction. Multimodal approaches can be used for meaningful engagement for literacy instruction for all students. Literacy support activities were linked to Howard Gardner's theory of multiple intelligences. Forty-one first grade participants were included in this study. This research was conducted during the participants' guided reading block and Response to Intervention time. The research indicates a multisensory, multimodal, multimedia approach to comprehensive literacy instruction results in high levels of student engagement in learning with iPads, as well as increased academic reading achievement.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. [29] leaves. Includes bibliographical references (leaves [28-29]).
Keywords: Literacy; Reading (Elementary); Educational technology; Computer-assisted instruction; iPads; First grade (Education); Language arts (Elementary); iPad; Reading